PENGARUH MOTIVASI DAN SEMANGAT KERJA TERHADAP KINERJA KARYAWAN PADA DINAS KOPERASI DAN USAHA MIKRO KOTA DEPOK - Farihatunnada (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
This research is motivated by the influence of motivation and work enthusiasm on employee performance at the Department of Cooperatives and Micro Enterprises in Depok City. This is done to see how much the level of motivation and morale on employee performance. The research method used is a quantitative method because it is a method used to determine the relationship or influence between two or more variables. Data collection technique through questionnaires distributed to 66 respondents using probability sampling technique with simple random sampling. In analyzing the data, using Instrument Test, Classic assumption test and Hypothesis Test. The results showed that the coefficient of determination was 0.652, which means that 65.2% of the contribution of the Variables of Motivation (X1) and Morale (X2) affect Employee Performance (Y). The conclusion from the data analysis above is that there is a positive and significant influence of Motivation and Work Enthusiasm on Employee Performance at the Department of Cooperatives and Micro Enterprises in the City of Depok.